On Inequality of Rights in Agricultural Land Privatization - Aleksandrovich Mayboroda, Victor (International Journal of Engineering and Technology, 2018)
The article examines the institution of agricultural land privatization. Considering the dynamics of modern legislation, considerable attention is paid to the historical overview of the development of regulatory developments in this institution. Currently, due to uncertain meaning of the term "privatization", the author emphasized its semantic content in regulating land relations in general and in connection with the turnover of agricultural land, in particular through the application of content analysis methods in normative materials. In addition, the land purchase was compared with certain provisions of foreign legal systems. The study has led to conclusions regarding the need for formation of independent law enforcement practices for privatization of agricultural land for agricultural use. The author suggests using this term if there is a regional norm on privatization. At the same time, if the regional legislation establishes the date for privatization commencement beyond an obvious planning horizon and does not allow the use of this particular institution, the author offers to transform public property into private using the institution to purchase land granted on a lease basis. The current application of the institute of public land privatization for agricultural use lacks the opposition of semantic burden of privatization to other forms of transformation of public possession into private property. The absence of such opposition in a law enforcement practice provides an opportunity for confusion of privatization and land purchase when considering specific disputes. Today, those participating in privatization, i.e. persons who can potentially purchase publicly owned lands, are in unequal conditions with regard to other methods of acquiring public lands, including through purchase in case of a bona fide rent. The study itself aims to understand the results of public land transformation into private land based on a priori provision on the need to form a competitive environment for the existence of various forms of ownership through economic regulation methods, avoiding the provision of legal advantages to individual forms of ownership.Â Â Â